Multifunctional Antibodies Are Induced by the RTS,S Malaria Vaccine and Associated With Protection in a Phase 1/2a Trial - Kurtovic, Liriye; Atre, Tanmaya; Feng, Gaoqian; Wines, Bruce D; Chan, Jo-Anne; Boyle, Michelle J; Drew, Damien R; Hogarth, P Mark; Fowkes, Freya J I; Bergmann-Leitner, Elke S; Beeson, James G (The Journal of infectious diseases, 2021)
Abstract Background RTS,S is the leading malaria vaccine candidate but only confers partial efficacy against malaria in children. RTS,S is based on the major Plasmodium falciparum sporozoite surface antigen, circumsporozoite protein (CSP). The induction of anti-CSP antibodies is important for protection; however, it is unclear how these protective antibodies function. Methods We quantified the induction of functional anti-CSP antibody responses in healthy malaria-naive adults (N = 45) vaccinated with RTS,S/AS01. This included the ability to mediate effector functions via the fragment crystallizable (Fc) region, such as interacting with human complement proteins and Fcγ-receptors (FcγRs) that are expressed on immune cells, which promote various immunological functions. Results Our major findings were (1) RTS,S-induced antibodies mediated Fc-dependent effector functions, (2) functional antibodies were generally highest after the second vaccine dose, (3) functional antibodies targeted multiple regions of CSP, (4) participants with higher levels of functional antibodies had a reduced probability of developing parasitemia following homologous challenge (P < .05), and (5) nonprotected subjects had higher levels of anti-CSP IgM. Conclusions Our data suggest a role for Fc-dependent antibody effector functions in RTS,S-induced immunity. Enhancing the induction of these functional activities may be a strategy to improve the protective efficacy of RTS,S or other malaria vaccines. Clinical Trials Registration NCT00075049 The leading malaria vaccine, RTS,S, induced antibodies that mediate various Fc-dependent effector functions. High levels of antibodies with multiple functional activities were associated with protection against homologous malaria challenge. This provides valuable insights for improving RTS,S or future malaria vaccines.